Attitudes of Engineering and Technology Teachers Towards the Use of Humanoid Robots in Education - Andrej Flogie; Jakob Škrobar; Dejan Zemljak (International Journal of Management, Knowledge and Learning)
Purpose: The aim of the study was to investigate the attitudes of teachers of technical and engineering subjects towards the use of humanoid robots in the learning process. The aim was to find out whether these teachers are more willing to integrate robots in the classroom than teachers of other subjects, and whether they perceive concrete possibilities to use robots in different learning situations (e.g. substituting in the absence of a student).